COST ANALYSIS OF SAHABAT RETAIL STORE JAMBI - Hassadi, Irfan; Aliludin, Arson (Journal of Business and Management, 2017)
Abstract. Sahabat retail store is one of retail store located in Jambi province. This store has build in 1991 by Mr. Anditoni. This store has 3 level of building with 5m width and 17m length. This retail has sold nine categories of products, which are, bed cover, sarong, batik sarong, women pray kit, prayer rugs, blanket, mosquito net, bolster case, and pillowcase. This store got the item from suppliers that located in Jakarta. Until 2016, this store not has a good cost management. Because of this by doing cost analysis of sahabat retail store especially in 2016, it will help the owner made a good cost management for the future. As the result of the analysis, this store has revenue Rp.506.272.000. in 2016; this store also spent Rp.495.317.027 as cost. This cost divided into 2 kinds, operational cost, and merchandise cost. Operational costs take Rp.183.827.027 and merchandise cost take Rp.311.490.000. In 2016, the store has BEP level 3.932 unit and Rp.474.792.055 for BEP level in Rupiah. They have reached their BEP level in 2016. The unit cost of each product is in table 3, the range between Rp.15.902 to Rp.389.588. They also can gain Profit Rp.10.954.973 in 2016.Key words: Cost analysis, break-even point, managerial accounting, retail